KAJIAN DELAPAN STANDAR NASIONAL PENELITIAN YANG HARUS DICAPAI PERGURUAN TINGGI - Anisa Fitri; Syahrani (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
The existence of national standards makes this standard not only applicable to campuses in certain areas. But nationally, so long as the campus is standing in the jurisdiction of the Republic of Indonesia. So this standard becomes a reference that must be obeyed and fulfilled. The existence of national standards in the conduct of research will certainly help achieve the research objectives. Universities must prepare standards consisting of National Standards for Higher Education in the field of Education, National Standards for Higher Education in the field of Research, National Standards for Higher Education in the field of Community Service, and Higher Education Standards in other fields, in accordance with the needs of universities in implementing the Tridarma of Higher Education to achieve university vision. College is not just a place for people to gain knowledge. But also become one of the contributors in developing science and technology in the country and also in the world. In accordance with applicable regulations, universities are expected to be able to support the implementation of research and community service. It is also intended to develop science and technology earlier. To support the achievement of these goals, there are a number of National Research Standards that must be understood and fulfilled by every university. It is hoped that with national standards like this, universities will not be careless in conducting research. However, it can ensure that the research and community service conducted is of good quality. At the same time the focus is on supporting research and community service goals.